Jurisprudence of verses from the book of Al-Hawi by Imam Al-Mawardi (deceased in 450 HA) Breastfeeding book (Collection and Study) - Al-Safari, Maryam Saad (Journal of Islamic Sciences, 2025)
This research aims to trace, collect, and study the verses of rulings from the book "Al-Hawi Al-Kabir" (The Great Book of Breastfeeding). It is part of an integrated project aimed at producing a book of verses of rulings, extracted from a book considered an encyclopedia of Islamic jurisprudence. I relied on the analytical inductive approach. The research included important topics, including a biography of Al-Mawardi (may God have mercy on him), an introduction to his book "Al-Hawi," a collection of verses of rulings in the book of Breastfeeding, the issues contained therein, and a study of them in the dedicated section. The research reached several conclusions, the most important of which are: The jurisprudence of verses of rulings derives its importance from its connection to the most important and primary sources of legislation, the Book of God Almighty, and from the scholars’ clear keenness to derive evidence from Quranic verses and derive jurisprudential rulings from them. This is evidenced by the derivation of a number of jurisprudential rulings from a single verse in the Holy Quran, even if it does not explicitly refer to a jurisprudential ruling.